PENGELOLAAN ARSIP DINAMIS INAKTIF DI KANTOR PERTANAHAN KABUPATEN SLEMAN - , RASYID IKHSANDHI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Writing final report entitled Managing Inactive records in Kantor Pertanahan Kabupaten Sleman Yogyakarta is the result of data collection Field Work Practices are held in Kantor Pertanahan Kabupaten Sleman D.I.Yogyakarta. Field Work Practice aims to identify inactive records managing system in the inactive file storage space. Handling the record consists of several stages, ranging from sorting the record, the record identification, handling, can be used to archive the record users, and record retrieval. Methods of data collection through there stages. First, the literature study to obtain reference data based on a clear and reliable sources in sccordance with the chosen theme. The second and third observations in the form of interviews. The second phase was conducted to gain an understanding of filing systems that run in the institute. After the method of data collection is done, the data are evaluated and then processed to obtain data relevant to the topic of discussion. The main conclusions overall managing inactive records in Kantor Pertanahan Kabupaten Sleman has been pretty good, but the management is still not optimal. This is because the minimum specialized human resources to manage the archive, save space and limited infrastructure.